Enhanced recovery of postoperative nursing for single-port thoracoscopic surgery in lung cancer patients - Hu, Xiufen; He, Xiaodan (Frontiers in Oncology, 2023)
Lung cancer is a common clinical malignant tumor, and the number of new lung cancer patients is increasing year by year. With the advancement of thoracoscopy technology and equipment, the scope of application of minimally invasive surgery has expanded to almost all types of lung cancer resection, making it the mainstream lung cancer resection surgery. Single-port thoracoscopic surgery provides evident advantages in terms of postoperative incision pain since only a single incision is required, and the surgical effect is similar to those of multi-hole thoracoscopic surgery and traditional thoracotomy. Although thoracoscopic surgery can effectively remove tumors, it nevertheless induces variable degrees of stress in lung cancer patients, which eventually limit lung function recovery. Rapid rehabilitation surgery can actively improve the prognosis of patients with different types of cancer and promote early recovery. This article reviews the research progress on rapid rehabilitation nursing in single-port thoracoscopic lung cancer surgery.